2016
DOI: 10.1590/1517-869220162205159722
|View full text |Cite
|
Sign up to set email alerts
|

Transtibial Versus Anteromedial Portal Techniques in Acl Reconstruction

Abstract: Introduction: Although the results of anterior cruciate ligament (ACL) reconstruction are well documented in many studies, with good to excellent outcomes in most cases, some issues like tunnel positioning are still discussed and studied. Objective: To compare the objective and subjective clinical outcomes of ACL reconstruction using the transtibial and anteromedial portal techniques. Methods: Prospective randomized study of 80 patients undergoing anterior cruciate ligament reconstruction by the same surgeon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…In total, 4 studies analyzed the use of drilling techniques and their association with the risk of revision 15,17,24,71 and complications. 6,17,45 No differences in revision and complication rates were reported between both groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 4 studies analyzed the use of drilling techniques and their association with the risk of revision 15,17,24,71 and complications. 6,17,45 No differences in revision and complication rates were reported between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 25 clinical studies, ** † † 4 (16% of all clinical studies) reported the incidence of revision. 16,17,24,71 The overall revision rate was 5.9% (442/7498 patients) in the AM group and 6.2% (94/1508 patients) in the TT group. Metaanalysis revealed no significant differences between the groups (n ¼ 9006; OR, 1.05 [95% CI, 0.76-1.45]; P ¼ .76) (Figure 5).…”
Section: Revisionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Radiological Outcomes. Independently drilled tunnels were significantly shorter (6 RCTs 14,16,34,37,39,51 : MD, 8.72; P ¼ .001) and were placed closer to the native ACL footprint. These results were strengthened by the sensitivity analysis excluding the studies of Han et al 17 and Hussin et al, 23 which used a modified TT technique (Supplemental Figure S5).…”
Section: Outcomes Of Independent Versus Tt Drillingmentioning
confidence: 94%
“…Subanalyses evaluating the best technique among the different independent drilling approaches showed that the AM portal technique had the highest Lysholm score (11 RCTs b : MD, 0.68; P ¼ .001) and Tegner score (6 RCTs 6,13,17,35,39,51 : MD, 0.27; P ¼ .004) versus the TT approach, while statistical significance was not reached with the IKDC subjective (8 RCTs 6,13,16,17,22,23,34,51 AM portal technique was seen for the results of both the Lachman and pivot-shift tests (P ¼ .08 and .09, respectively). The sensitivity analysis excluding the 2 RCTs 17,23 with a modified TT technique confirmed all the previous differences, and both the Lachman and pivot-shift tests reached statistical significance in favor of the AM portal technique (P ¼ .03 and .04, respectively).…”
Section: Outcomes Of Different Independent Drilling Techniquesmentioning
confidence: 99%